2022
DOI: 10.1155/2022/9072082
|View full text |Cite|
|
Sign up to set email alerts
|

Association between Perceived Salt Intake and Arterial Stiffness

Abstract: To explore the association of perceived salt intake (SI) level with arterial stiffness in the community population in northern China. We enrolled participants who completed the health questionnaire, physical examination, and brachial-ankle pulse wave velocity (baPWV) test during 2010-2019 and divided them into <6 g (low SI), 6-10 g (medium SI), and >10 g (high SI) groups based on their daily SI. The influence of SI on baPWV was analyzed using the multivariate logistic regression model. A total of 36324 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Thus, preventing arterial stiffness seems reasonable in improving cardiovascular health. In the literature, various nutritional interventions regarding arterial stiffness have recently been widely discussed [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , …”
Section: The Impact Of Diet On Arterial Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, preventing arterial stiffness seems reasonable in improving cardiovascular health. In the literature, various nutritional interventions regarding arterial stiffness have recently been widely discussed [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , …”
Section: The Impact Of Diet On Arterial Stiffnessmentioning
confidence: 99%
“…For example, the cohort study of the Chinese population ( n = 36,324 subjects, aged 49.10 ± 12.57 years) analyzed the influence of various amounts of sodium intake (low sodium <6 g, medium 6–10 g, and high >10 g daily) on arterial stiffness. The high sodium intake (>10 g/day) revealed a deleterious effect on arterial stiffness (baPWV ≥ 1400 cm/s) [ 105 ]. Conversely, reduced sodium intake decreases blood pressure and alleviates arterial stiffness.…”
Section: The Impact Of Diet On Arterial Stiffnessmentioning
confidence: 99%
“…Salt intake was assessed using a questionnaire survey; participants were asked to evaluate their salt intake and classify their daily habitual salt intake as low, moderate, or high. Previous cohort studies have confirmed that the 24‐h urinary sodium excretion corresponding to low, moderate, and high salt intake are <6 g, 6–10 g, and >10 g, respectively 13–16 . Physical activity was defined as the frequency of physical activity during leisure time (≥30 min/time, ≥3 times/week).…”
Section: Methodsmentioning
confidence: 99%
“…Previous cohort studies have confirmed that the 24‐h urinary sodium excretion corresponding to low, moderate, and high salt intake are <6 g, 6–10 g, and >10 g, respectively. 13 , 14 , 15 , 16 Physical activity was defined as the frequency of physical activity during leisure time (≥30 min/time, ≥3 times/week). The occupation category was defined as (1) blue collar and (2) white collar.…”
Section: Methodsmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%